Estudo de bicamadas FM/AF e válvulas de spin por ressonância ferromagnética - Thiago Eduardo Pedreira Bueno (2014)
The theme of this work is the investigation of magnetic phenomena of metallic multilayers composed of ferromagnetic (FM), antiferromagnetic (AF) and nonmagnetic (NM) layers. We have fabricated by sputtering FM/AF (Py/IrMn) bilayers, which present exchange bias and spin valves (FM/NM/FM/AF - Py/Ru/FeCo/IrMn) that exhibit bilinear coupling between FMs layers. The e ects of the tilt angle of the sample relative to the evoparation direction as well as the in uence of a magnetic eld applied during lm growth were explored. Samples prepared under these conditions may show strong uniaxial anisotropy and the control of such properties is of great interest. Magnetic properties of these systems have been characterized by ferromagnetic resonance (FMR). These measurements yield two important parameters: the ferromagnetic resonance eld HR , whose analysis of the angular dependence in lm plane HR allows the determination of the e ective magnetic anisotropy eld; and the line widths H , which provide the magnetization relaxation mechanisms by studying its angular dependence H . A method was developed to control the direction of the exchange bias anisotropy in FM/AF bilayers fabricated by oblique deposition assisted by magnetic eld ! H 0 . It was found that the inclination between the evaporation direction and the substrate normal determines the uniaxial anisotropy direction of the ferromagnetic layer due to the self shadowing e ect. The rst deposited FM layer (Py) grows magnetized parallel to the applied eld. By depositing the antiferromagnetic material (IrMn), the magnetic moments of its rst layers allign to the Py layers by the exchange interaction, and the rest of this layer grows in a well-determined direction of antiferromagnetic anisotropy. Spin valves were fabricated without an applied magnetic eld in a magnetron sputtering system which has two fundamental inclinations, with strong in uence on the sample properties: (i) the tilt angle between the magnetron sources and the substrate, which is responsible to induce strong uniaxial anisotropy; (ii) the angle between adjacent magnetrons, which is responsible to inducing noncollinear uniaxial anisotropy axes. The induced non-collinearity of the magnetic anisotropies was identi ed and quanti ed by FMR measurements. This work shows the possibility to design and fabricate spin valves with well-de ned directions of the axes of the uniaxial ferromagnetic layers.